Nitrogen and carbon contents, nitrogen use efficiency, and antioxidant responses of perennial ryegrass accessions to nitrogen deficiency. (21st October 2019) - Yao, Yanyu; Zhang, Cankui; Camberato, James J.; Jiang, Yiwei
Abstract: The study was designed to investigate nitrogen and carbon contents, nitrogen use efficiency, and antioxidants of a tolerant accession PI231578 (TOL) and a susceptible PI306292 (SUS) of perennial ryegrass subjected to 7.5 mM N (control) and 0.75 mM N (low) for 6, 12, and 20 d in a growth chamber. The SUS had decreased plant height, dry matter, shoot carbon content and showed more reductions in leaf chlorophyll and shoot N content at 6, 12 d or 20 d of low N. An increased N use efficiency was greater in the shoots of SUS during the low N treatments and in the roots of TOL at 20 d. Shoot soluble protein content (TSP) was unaffected in TOL but decreased in SUS at 20 d of low N, whereas shoot catalase activity decreased in SUS. Root superoxide dismutase and peroxidase activities increased in TOL at 20 d of low N.